Preparation and Characterization of Transdermal Therapeutic System Containing Simvastatin: A Statistical Study - Mishra, Santosh Kumar; Kumar, Rahul; Patil, Purushottam Ramchandra; Gupta, Rishiksh; Mahor, Alok; Bhardwaj, Peeyush (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: The purpose of the present study was to design, develop, and characterize the transdermal patches containing Simvastatin for the management of blood lipid levels. Materials and Methods: Transdermal patches of Simvastatin were prepared by the solvent casting method. The prepared patches were evaluated for physicochemical characteristics such as thickness, weight variation, folding endurance, percentage moisture uptake, percentage moisture content, percentage drug content, and ex-vivo permeation study. Eudragit polymer grades ERL100 and ERS100 were used in 6:4 and 8:2 ratio to prepare the formulations. Formulations were prepared using 23 factorial designs. Stability studies of the films were subjected to the environmental conditions at a temperature of 45°C, 75% relative humidity for 45 days. Results: The permeation parameters like flux, amount of drug permeated, and permeability coefficient were obtained. It was found that all these values were highest for formulation F8. Conclusion: Based on all parameters, formulation F8 was considered as the best formulation.
Keywords: Transdermal patches; Simvastatin; Factorial designs; Matrix; Eudragit